POLA MANAJEMEN PENGEMBANGAN KOMPETENSI DOSEN DALAM PEMBELAJARAN DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MEDAN - Yusnadi .; Nasrun .; Apiek Gandamana (Universitas Negeri Medan, 2016)
Abstract: Patterns of Competence Development Management Lecturer in Learning Faculty of Education, University of Medan. The general objective to determine the pattern of management competency development in learning lecturer in the Faculty of Education (FIP), State University of Medan (UNIMED). Data were collected through observation, interviews and documentation. Analyzed using the steps: data reduction, data presentation, and conclusion. The results showed that, first, planning the development of professional competence and pedagogical faculty has gained the attention and involvement of the chairman Prodi. Second, Prodi monitoring directed at the faculty competence development. Third, the implementation of control performance of lecturers and study programs.Keywords: Management, Competency, LearningAbstrak : Pola Manajemen Pengembangan Kompetensi Dosen Dalam Pembelajaran Di Fakultas Ilmu Pendidikan Universitas Negeri Medan. Tujuan umum untuk mengetahui pola manajemen pengembangan kompetensi dosen dalam pembelajaran di lingkungan Fakultas Ilmu Pendidikan (FIP) Universitas Negeri Medan (UNIMED). Data dikumpulkan melalui observasi, wawancara dan dokumentasi. Dianalisis dengan menggunakan langkah-langkah: reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa, Pertama, perencanaan pengembangan kompetensi pedagogi dan profesional dosen telah mendapat perhatian dan keterlibatan ketua prodi. Kedua, prodi melakukan pemantauan pengembangan kompetensi dosen diarahkan pada. Ketiga, pelaksanaan pengendalian kinerja dosen dan prodi.Kata Kunci : Manajemen, Kompetensi, Pembelajaran